Karts Area Mining and Social Conditions Communities - Wahyuddin Bakri; Suardi Laupe; Andi Muhammad Ikbal Salam (IAIN Parepare, 2023)
Karst is a very vital landscape, karst areas as natural destinations function as water buffers, are able to store water throughout the year and are useful in meeting the supply of clean water for the survival of the Maros people. The karst area around Salenrang Village has been exploited on a large scale and until now has affected the economic conditions of the community. The research aims to determine the impact of the socio-economic conditions of the community due to mining in the Karts area. The informants in this study consisted of government, community leaders, traditional leaders, environmentalists and the community. This research method is qualitative with an environmental sociology approach, the data collection technique is field research which is taken through observation, in-depth interviews and document review. While data analysis includes data collection, data presentation, data reduction, to conclusions.The results of research show that mining in Karts areas has a major impact on the economic life of the community so that it influences the sustainability of people's lives to the point of changing social structure, social interaction and economic conditions. The impact of mining in karts areas affects the condition of society both positively and negatively, positively mining Karts areas has an impact on reducing unemployment, opening up job vacancies, stimulating the development of social infrastructure such as places of worship, banking and markets and educational facilities, changing the mindset of industrial society. While the negative impacts of mining in Karts areas include environmental degradation, social conflicts due to economic injustice, and decreased farmers' income due to environmental damage.